Surface roughness of acrylic denture base resins polished with different abrasive agents: an in vitro study - Sharmista, Sreeram; Siva Kumar, Gudala; Ravisankhar, Yalavarthy; Srinivas, Kalluri; MVS, Hari Krishna; Kumar, Satyendra (International Journal of Dental Materials, 2020)
Background: Excessive surface roughness on the denture base can adversely impact the oral health of the patient. Therefore, it is necessary to polish the denture before they are delivered to the patient. The abrasive and polishing agents should provide a smoother surface without affecting the physical and mechanical properties of denture bases.Aim: This study aims to examine and understand the potential of different polishing materials on surface roughness of acrylic denture base resins.Materials and methods: A total of 60 Heat-cure acrylic specimens (acrylic bars) were made and grouped into six groups. Control (no abrasive), Pumice (Micro-white), Eggshell powder, Seashell powder, Black sand powder, White sand powder are used as abrasive materials for polishing these specimens. These polished specimens were subjected to profilometer surface roughness analysis.Results: The acrylic specimens polished with eggshell powder on acrylic specimens showed the least surface roughness followed by black sand, white sand, pumice and seashell powders. Tukey HSD showed significant differences (p=0.000) between unpolished and polished specimens.Conclusion: Eggshell powder effectively reduced the surface roughness of denture base resin material. However, the surface roughness demonstrated by all the abrasive materials used was within the threshold limit (2 µm). Therefore, all the materials can be used as abrasives.